PENGARUH PENDAPATAN ASLI DAERAH DAN PENGELUARAN PEMERINTAH TERHADAP ANGGARAN DAN BELANJA DAERAH KABUPATEN KERINCI - Ernita, Dewi; Zasrati, Masrida (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to find out: 1.) To find out if there is an influence between Local Original Income and Government Expenditure on Kerinci Regency Spending in 2011-2020. 2.) To find out how much influence between Local Original Income and Government Expenditure on Kerinci District Revenue and Spending Budget 2011-2020. 3.) To find out which factors have the most influence between Local Original Income and Government Expenditure on the Kerinci District Revenue and Spending Budget in 2011-2020.The data collected in this study in the form of secondary data, namely data on Regional Original Income, Government Expenditure and Kerinci District Revenue and Spending Budget from 2010 to 2019. The data analysis tool used is Multiple Linear Regression Analysis. There is a significant influence on the Regional Original Lumsing Budget and Kerinci Regency Spending in 2010-2019. This can be proven by thitung ? ttabel (2,290) ? (2,365) with a significant increase of 0.056 > 0.05. There is a significant influence on the regional revenue and spending budget. This can be proven by thitung ? ttabel (9,202) ? (2,365) with a significant rate of 0.000 < 0.05. There is a significant influence between Local Original Income and Government Expenditure on the Kerinci District Revenue and Spending Budget in 2010-2019. This can be proven by the calculated F value of 604,200 ? F table 4.737 or the significance value of 0.000 ? 0.05. Large Influence of Local Original Income and Government Expenditure on Kerinci District Revenue and Spending Budget in 2010-2019. The effect of Regional Original Income (X1) on the Regional Revenue and Spending Budget (Y) was partially 19.24%. The effect of Government Expenditure (X2) on the Regional Revenue and Spending Budget (Y) is partially 80.16%. The effect of Local Original Income (X1) and Government Expenditure (X2) simultaneously on the Regional Revenue and Spending Budget (Y) is 99.4% and the remaining 0.6% is influenced by other factors outside of this study